Feature level fusion of range and intensity images of an object. (29th June 2009) - Pati, Umesh C.; Dutta, Pranab K.; Barua, Alok
This paper presents feature level fusion of images of an object obtained from two different imaging techniques. A draft 3-D view of the object is generated by registering range images obtained from scanning the object by a laser beam. For that purpose, the method of optical triangulation is employed for data acquisition and feature matching technique for the registration of the images. Triangle-based linear interpolation is used to obtain a 3-D mesh representing the object surface. Structural features are extracted from the draft 3-D model of the object and subsequently mapped to 2-D plane by perspective transformation. Hough transform technique has been implemented for the extraction of structural features from the intensity image of the object obtained under illumination light. Fusion of both the extracted edge maps is accomplished by affine transformation after identifying a set of control points. This provides a high-level description of the object.